Oxygen Delivery as a Limiting Factor in Modelling Dicopper(II) Oxidase Reactivity. Issue 29 (16th February 2017) - Gülzow, Jana; Hörner, Gerald; Strauch, Peter; Stritt, Anika; Irran, Elisabeth; Grohmann, Andreas
Abstract: Deprotonation of ligand‐appended alkoxyl groups in mononuclear copper(II) complexes of N, O ligandsL1 andL2, gave dinuclear complexes sharing symmetrical Cu2 O2 cores. Molecular structures of these mono‐ and binuclear complexes have been characterized by XRD, and their electronic structures by UV/Vis, 1 H NMR, EPR and DFT; moreover, catalytic performance as models of catechol oxidase was studied. The binuclear complexes with anti ‐ferromagnetically coupled copper(II) centers are moderately active in quinone formation from 3, 5‐di‐ tert ‐butyl‐catechol under the established conditions of oxygen saturation, but are strongly activated when additional dioxygen is administered during catalytic turnover. This unforeseen and unprecedented effect is attributed to increased maximum reaction rates v max, whereas the substrate affinity K M remains unaffected. Oxygen administration is capable of (partially) removing limitations to turnover caused by product inhibition. Because product inhibition is generally accepted to be a major limitation of catechol oxidase models, we think that our observations will be applicable more widely. Abstract : The more you give, the more you get : Periodic administration of additional dioxygen to solutions previously saturated in O2 dramatically enhances catalytic turnover in a number of new as well as established synthetic di‐copper(II) catechol oxidase models. Micro‐bubbles ("bubbly flows") are identified as an efficient reservoir of dioxygen that has previously not been accounted for (see scheme).